Scan time reduction in 23Na-magnetic resonance imaging using the chemical shift imaging sequence: evaluation of an iterative reconstruction method - Weingärtner, Sebastian; Fatar, Marc; Neumaier-Probst, Eva; Schad, Lothar R. (Zeitschrift für medizinische Physik, 2015)
To evaluate potential scan time reduction in 23Na-Magnetic Resonance Imaging with the chemical shift imaging sequence (CSI) using undersampled data of high-quality datasets, reconstructed with an iterative constrained reconstruction, compared to reduced resolution or reduced signal-to-noise ratio. CSI 23Na-images were retrospectively undersampled and reconstructed with a constrained reconstruction scheme. The results were compared to conventional methods of scan time reduction. The constrained reconstruction scheme used a phase constraint and a finite object support, which was extracted from a spatially registered 1H-image acquired with a double-tuned coil. The methods were evaluated using numerical simulations, phantom images and in-vivo images of a healthy volunteer and a patient who suffered from cerebral ischemic stroke. The constrained reconstruction scheme showed improved image quality compared to a decreased number of averages, images with decreased resolution or circular undersampling with weighted averaging for any undersampling factor. Brain images of a stroke patient, which were reconstructed from three-fold undersampled k-space data, resulted in only minor differences from the original image (normalized root means square error < 12%) and an almost identical delineation of the stroke region (mismatch < 6%). The acquisition of undersampled 23Na-CSI images enables up to three-fold scan time reduction with improved image quality compared to conventional methods of scan time saving.